Levodopa-induced modulation of subthalamic beta oscillations during self-paced movements in patients with Parkinson's disease. - Doyle, L; Kühn, A; Hariz, M; Kupsch, A; Schneider, G; Brown, P (2005)
Excessive synchronization of neural activity in the beta frequency band ( approximately 20 Hz) within basal ganglia circuits might contribute to the paucity and slowness of movement in Parkinson's disease (PD). Treatment with dopaminergic drugs reduces the background level of beta frequency band synchronization in the subthalamic nucleus (STN), but has not been shown to increase the proportion of beta activity that is suppressed before voluntary movement in PD. We assessed changes in the event-related desynchronization (ERD) in the beta frequency band of local field potential signals from the region of the STN in 14 patients with PD as they performed self-paced movements of a joystick before and after levodopa administration. The dopamine precursor, levodopa, increased the duration and magnitude of the premovement beta ERD, but did not alter postmovement synchronization in the beta band. Both the latency and magnitude of the beta ERD inversely correlated with the degree of motor impairment. These findings suggest that the beta ERD recorded in the STN area reflects motor-preparative processes that are at least partly dependent on dopaminergic activity within the basal ganglia.